Comparative Assessment of Melatonin Implants and Progesterone Hormone Effect on the Testicular Changes in Tomcats - Thabit, Mohammed; Mahdi , Salah (University of Thi-Qar Journal of agricultural research, 2025)
The purpose of study to evaluate the effectiveness of melatonin implants and progesterone hormone as non-surgical methods for controlling reproductive activity in adult male cats. Twenty-four healthy toms, aged 3–4 years, were equally divided into three groups: a control group, a melatonin-treated group (18mg S.C.) and progesterone-treated group (megestrol acetate 2.5 mg every 10 days for two months). All cats were housed in comparable environmental conditions, and behavior observations as well as serum testosterone concentrations were taken 20, 40 and 60 days after treatment.melatonin implants and progesterone hormone both led to testicular regression (p <0.05) of treated tom cats comparative to control. Testicular length and width, scrotal circumference, seminiferous tubule diameter, interstitial tissue thickness, number of interstitial cells, and height of germinal epithelium all showed a gradual decrease over the course of 60 days. Regression was modest with melatonin (MLT) and stronger and earlier with progesterone. By day 60, testicular length and width decreased to approximately 17 mm (MLT) and 14 mm (in P4-treated cats), while scrotal circumference was reduced to 2.44 cm (MLT) and 1.52 cm (P4-treated). Histologically, melatonin led to a gradual vacuolation and desquamation of germ cells, whereas progesterone induced marked seminiferous atrophy, change of spermatogenic cells and expansion of the interstitium. There were no local or systemic adverse reactions. Results indicate that both have an inhibitory effect on testicular structure and reproductive activity, the suppression being reversible and progesterone having more potent inhibition.